Foreign Body Aspiration in Pregnancy - Andrew L. Atkinson; Joseph Canterino (Hindawi Limited, 2012)
A 24-year-old morbidly obese African American gravida 1, with a history of severe asthma complicated by multiple inpatient admissions, presents at 30 weeks gestation with a foreign body in her left main stem bronchus. After a failed bronchoscopy postpartum, the patient slipped into respiratory failure and was subsequently intubated, spending two weeks in the intensive care unit. After two more attempts of trying to retrieve the foreign object from her lung via bronchoscopy, she eventually contracted a postobstructive pneumonia and underwent a left lower lung lobectomy for curative treatment.